Prototyping Web instruments with Mosaicode - Gomes, André; Resende, Frederico; Gonçalves, Luan; Schiavoni, Flávio Luiz (Anais do Simpósio Brasileiro de Computação Musical (SBCM), 2019)
Many HTML 5 features enable you to build audio applications for web browsers, simplifying the distribution of these applications, and turning any computer, mobile, and portable device into a digital musical instrument. Developing such applications is not an easy task for layprogrammers or non-programmers and may require some effort by musicians and artists to encode audio applications based on HTML5 technologies and APIs. In order to simplify this task, this paper presents the Mosaicode, a Visual programming environment that enables the development of Digital Musical Instruments using the visual programming paradigm. Applications can be developed in the Mosaicode from diagrams – blocks, which encapsulate basic programming functions, and connections, to exchange information among the blocks. The Mosaicode, by having the functionality of generating, compiling and executing codes, can be used to quickly prototype musical instruments, and make it easy to use for beginners looking for learn programming and expert developers who need to optimize the construction of musical applications.